2011
DOI: 10.1007/s00432-011-1046-5
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide-mediated glioblastoma cell death: dependent or independent on the expression of its target, topoisomerase II alpha?

Abstract: In vitro, the levels of TopoIIa protein expression correlate with response to etoposide but also multiple molecular events namely DNA-PK and MDR also play a role in cell sensitivity to etoposide. That we did not find a high expression of TopoIIa in clinical specimens further suggests the mechanisms underlying treatment response are complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A number of studies have thus far shown an association between levels of topoisomerase expression and cellular susceptibility to TOP2 poisons ( 48 , 49 ). TOP2A suppression is thought to result in resistance by decreasing the amount of enzyme-DNA complex, in turn decreasing the amount of DNA damage ( 42 ).…”
Section: Topoisomerase Poison Susceptibility: Biomarkers To Personalimentioning
confidence: 99%
“…A number of studies have thus far shown an association between levels of topoisomerase expression and cellular susceptibility to TOP2 poisons ( 48 , 49 ). TOP2A suppression is thought to result in resistance by decreasing the amount of enzyme-DNA complex, in turn decreasing the amount of DNA damage ( 42 ).…”
Section: Topoisomerase Poison Susceptibility: Biomarkers To Personalimentioning
confidence: 99%
“…TOP2 protein level is known to correlate with susceptibility to etoposide treatment in cancer 19 and specifically in glioma cell lines, 20 yet it is not known whether TOP2 expression defined by Sonabend et al: Convection-enhanced delivery of etoposide its transcript levels also correlates with susceptibility to etoposide. This is important given that the characteristic expression of this gene in PN glioblastoma in the database of TCGA was determined based on RNA expression array.…”
Section: Topoisomerase Iib Transcript Levels Correlate With Susceptibmentioning
confidence: 99%
“…With higher TOP levels being potentially accountable for enhanced drug sensitivity (Burgess et al , ; MacGrogan et al , ; Sevim et al , ), we determined whether differential expression of TOP2A and TOP2B, the two major isoforms of human TOP2, might be regulated by HMGA2 and thus could be responsible for the Etop treatment outcome. Western blot analysis revealed that the observed protective effect was not due to changes in TOP2A/B expression levels that consistently correlated with HMGA2 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%